The Influence of Regulation, Audit Delay, Audit Fees, and Firm Size on Auditor Switching in Transportation and Logistics Entities Listed on The Idx from 2018 to 2022 - Susanti, Gusti Ayu Puji; Fitriyah, Nur (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to demonstrate the impact of regulations, audit delay, audit fees, and firm size on auditor switching. The subjects of this observation are transportation and logistics entities listed on the Indonesia Stock Exchange during the period 2018-2022. The sampling method used is purposive sampling, resulting in 55 observation samples. The analysis in this study employs logistic regression analysis. The tool used is Eviews version 13. The results of the study prove that the variables of regulation, audit delay, audit fees, and firm size do not influence auditor turnover individually. However, when tested together, these variables collectively influence auditor turnover with a percentage of 31.6%, while the remaining 68.4% is explained by variables other than those observed.